ANALISIS UNJUK KERJA KOLEKTOR SURYA PELAT DATAR DENGAN PENAMBAHAN SIRIP BERLUBANG BERDIAMETER BEDA SEBAGAI NOSEL YANG DISUSUN SECARA STAGGERED - Ketut Astawa; I N Suarnadwipa; I GN Tenaya; Agus Junianto (Jurnal Ilmiah Teknik Mesin POROS, 2021)
The solar collector is a device that collects solar radiation and converts it into useful heatenergy. Several types of solar collectors include the parallel flow flat plate solar collector and theperpendicular flow absorber plate solar collector. Previous design of flat plate solar collectorperpendicular flow absorber plate usually uses plates with the same hole diameter. To improve theperformance of this solar collector, modifications have been made by adding perforated fins withdifferent diameters which are arranged staggeredly as an air flow channel or nozzle. The intendedmodification of nozzle diameter is to make the nozzle diameter size different from the large diameter nearthe inlet to the small diameter near the oulet and compared to the reverse nozzle position. Making thediameter of the nozzle near the inlet is larger than the diameter of the hole near the outlet aims to makethe mass flow of air passing through the hole near the inlet larger, so that the flow of air massesexperiences more heat transfer while the diameter of the hole near the outlet is made small is to reducethe mass flow of air which is wasted faster through the outlet channel. With the variation of the holediameter from large to small, it is expected that the heat transfer that occurs in the solar collector will bemore optimal, but it should also be seen in the reverse position. The research was carried outexperimentally. The results of his research show that the useful energy and efficiency of solar collectorswith large to small diameter slotted fins are higher than those with small to large diameter slotted fins.